Hsp90 Binds Directly to Fibronectin (FN) and Inhibition Reduces the Extracellular Fibronectin Matrix in Breast Cancer Cells - Hunter, Morgan C.; O’Hagan, Kyle L.; Kenyon, Amy; Dhanani, Karim C. H.; Prinsloo, Earl; Edkins, Adrienne L. (PloS one, 2014)
Heat shock protein 90 (Hsp90) has been identified in the extracellular space and has been shown to chaperone a finite number of extracellular proteins involved in cell migration and invasion. We used chemical cross-linking and immunoprecipitation followed by tandem mass spectrometry (MS/MS) to isolate a complex containing Hsp90 and the matrix protein fibronectin (FN) from breast cancer cells. Further analysis showed direct binding of Hsp90 to FN using an in vitro co-immunoprecipitation assay, a solid phase binding assay and surface plasmon resonance (SPR) spectroscopy. Confocal microscopy showed regions of co-localisation of Hsp90 and FN in breast cancer cell lines. Exogenous Hsp90β was shown to increase the formation of extracellular FN matrix in the Hs578T cell line, whilst knockdown or inhibition of Hsp90 led to a reduction in the levels of both soluble and insoluble FN and could be partially rescued by addition of exogenous Hsp90β. Treatment of cells with novobiocin led to internalization of FN into vesicles that were positive for the presence of the lysosomal marker, LAMP-1. Taken together, the direct interaction between FN and Hsp90, as well as the decreased levels of both soluble and insoluble FN upon Hsp90 inhibition or knockdown, suggested that FN may be a new client protein for Hsp90 and that Hsp90 was involved in FN matrix assembly and/or stability. The identification of FN as a putative client protein of Hsp90 suggests a role for Hsp90 in FN matrix stability, which is important for a number of fundamental cellular processes including embryogenesis, wound healing, cell migration and metastasis.